Underwater Hearing - Popper, A.; Ketten, Darlene (Elsevier, 2008)
This chapter examines the structure and function of hearing and the auditory system in fishes and marine mammals. Hearing is considered in terms of the evolution of the vertebrate auditory system in fishes and the readaption of mammals to the aquatic environment.